An evaluation of the quality of Ukay-ukay garments - Valdez, Jesse Dela Cruz
The Ukay-ukay business is the retailing of garments that are used or seconds. It has been gaining recognition in the Philippines. Places like Baguio City, Cubao, Carriedo, Greenhills, Cebu City, Puerto Princesa City and Tawi-tawi have emerged as havens of merchandise sold by these shops. In the aspect of garments, the Ukay-ukay (from the term "hukay", which means to dig or scavenge) merchandise are found to be either secondhand, a second, a surplus and/or even a relief good from charity. It is said that those who buy from them are just concerned with their buying power and not the quality (Barrameda, 2001). Likewise, those who usually buy from them are in the economic classes B and C (Tudlong, 1998). Nowadays, as discovered by the researcher even those belonging in the higher strata buy merchandise sold in Ukay-ukay garment shops. How come these clothes are still brought even if they are seconds and defective? What are the common defects? How are they classified? What is the nature of the Ukay-ukay garments' defects?? These are the questions the researcher attempted to answer in this study. The researcher tried to describe the quality of the ukay-ukay garments in terms of construction, identify the characteristics of the defects, and determine and classify the garments according to their quality. The main objective of this study was to describe the quality of ukay-ukay garments. To achieve this, the researcher went into a representative garments shop to gather data needed in meeting the objectives. The researcher used an evaluative research on the state of goods of ukay-ukay garments, the descriptive method in describing the nature of the garments, 30% inspection for the sampling procedure, and the descriptive statistical analysis for the treatment of data gathered. The researcher made a checklist based on standard quality checklists from different sources. The nature of defects were identified, the most recurrent determined and classified accordingly. The classification were as follows: construction, appearance and trims and notions. There were five (5) garment types that were inspected. They were men's sport shirt, men's T-shirt, men's denim pants, women's T-shirt, and women's pants. These garments types have the most number of stocks in the representative garment shop. For men's T-shirt, the most common construction defects were untrimmed excess thread from seams and stitches, bulky over edging, asymmetrical sleeve length, tight tension, and puckering. Based on appearance evaluation fuzz balls and inconsistent stitching were found. For the men's pants, the most common construction defects are untrimmed excess thread, and seam grin. For the appearance, the most common appearance defect was creased and wrinkled garment. For men's pants, the most common construction defects were untrimmed excess thread, bulky stitch, unfinished raw edge, asymmetrical pant length, puckering, seam grin, and too tight tension. For the appearance, the most common were untrimmed excess thread, bulky stitch, unsightly overlap of stitches, fizz balls, puckering, unpressed garments, and wrong shade after hanging or washing. The trims and notions on this men's garment type had recognizable defects, compared to the first two. The common defects were bubbles found on the fusible interfacing, puckering due to the attachment of the fastener and too big/small buttonhole. The common construction defects on women's T-shirt were misaligned seams and puckering. For the appearance, the most common were missing care labels and hangtags, fuzz balls, and unpressed garments. The most common construction defects on women's pants were asymmetrical pant length, too tight tension, seam grin, butterflied seams, puckering, and seam slippage. The common appearance defects were unsightly overlap of stitches, fuzz balls, wrong shade after washing or hanging, too tight tension, puckering, misaligned and top stitching. The most common trims and notions defect were the air bubbles found on the fusible interfacing.